149k views
5 votes
Solve using the substitution method.

x + 2y = 9

x + 3y = 13



(1, 4)

1 Answer

5 votes

Answer:

x = 1, y = 4

Explanation:

This is very simple

Since you have 2 equations with the same coefficient of x, just minus one equation from another:

x + 3y = 13

-

x + 2y = 9

1y = 4

Sub y = 4 into any of the 2 equation,

x + 3(4) = 13

x + 12 = 13

x = 13 - 12

= 1

User Somerandomusername
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.